Teachers’ Qualification, Attitude and Mastery of Content as Correlates of Students’ Academic Achievement in Economics in Lagos State, Nigeria - Ajayi, Kassim Olusanmi; Onibeju, Mufutau Olayinka; Olutayo, David Olanrewaju (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
Over the years, achievement in Senior Secondary School Economics has been a major concern to stakeholders in education because with its popularity, one would expect students taking the subject to do well and have distinctions. But this is not the case as many students performed below credit pass in the subject. Thus, this study investigated how teachers’ qualification, attitude and mastery of content correlates with students’ achievement in Senior Secondary Economic in Lagos State, Nigeria . A descriptive survey research design was adopted for the study. Multistage sampling technique was used to select a total of 30 public senior secondary schools and 600 students from three out of the five local government areas in Lagos East Senatorial District. Five research hypotheses were tested and answered using three instruments: Economics Achievement Test; (r = 0.76), Teachers’ Questionnaire - (Perceived Teachers’ Mastery of Content Scale; (r= 0.86), and Teachers’ Attitude Questionnaire; (r= 0.78), and Students’ Perceived Teachers’ Subject Mastery Questionnaire; (r = 0.88). Data were analysed using Pearson Product Moment Correlation Coefficient and Multiple Regression analyses. The results of the findings revealed that there is a significant relationship between teachers’ mastery of content and students’ achievement in Economics (r =0.507, P < 0.05) as well as between teachers’ attitude and achievement (r = .362, P < 0.05). However, no significant relationship was established between qualification and achievement (r = 0.77, P > 0.05). Based on these findings, it was recommended among others that teachers should equip themselves pedagogically through in-service training to enhance students’ academic achievement in Economics. Keywords : Teacher mastery of Content, Teacher Attitude, Teacher Qualification, Academic Achievement, Economics